Osteochondritis dissecans in bilateral lateral femoral condyle in knees() - Zekcer, Ari (Rev Bras Ortop, 2013)
The osteochondritis dissecans (OCD) is a disease of unknown cause that classically affects the knee lateral border of the medial femoral condyle. We present a rare case of OCD in bilateral lateral femoral condyle.